Anticariogenic potential and quantification of the enamel mineral elements around restorative materials - Leão, Isabela Furlaneto (2017)
Objective: The aim of this in vitro study was to evaluate the anticariogenic potential and quantification of the enamel mineral elements around restorative materials after pH-cycling, through the analysis of the microhardness of the enamel as well as the evaluation of Ca/P/F ratio by Energy-dispersive X-ray spectroscopy analysis (EDS). Methods: Ninety blocks of bovine enamel after polishing were submitted to analysis of the microhardness and analysis of the composition in EDS, and sequentially randomly divided into six groups according to the treatment used (n=15): F IX (Fuji IX Extra - GC Corporation); IZ (Ion Z - FGM); F II (Fuji II LC GC Corporation); B II (Beautifil II - Shofu); F250 (Filtek Z250 XT - 3M ESPE); and C (Control - No treatment). The specimens were subjected to pH-cycling for 7 days. Subsequently, they were analyzed by EDS, and the final evaluations of the microhardness at standard distances from the treatment material. Results: The EDS findings revealed that there was a significant increase in Fluor concentration and decrease in Calcium in Group BII after pH-cycling. The values of the surface microhardness in F IX, IZ and F II were higher than those in B II, F250 and C at different distances of the materials. Conclusion: According to the methodology used, it can be concluded that restorative materials F IX, IZ and F II were able to partially inhibit enamel demineralization under a dynamic pH cycling model. The giomer B II system demonstrated an intermediate anticariogenic potential and incorporation of fluoride in the enamel with statistical difference between Z250 and C, which did not show difference between them.